Academic resilience for preservice teachers among field of sciences: A measurement scale in education - Muhammad Bukhori Dalimunthe; Ery Tri Djatmika; Heri Pratikto; Puji Handayati; Rosmala Dewi; Siti Salina Mustakim (International Journal of Evaluation and Research in Education (IJERE), 2021)
The scale of measuring academic resilience in a decade has experienced rapid development. Numerous instruments have been formulated by previous researchers, but it has not explicitly measured the academic resilience for preservice teachers. The purpose is to construct a new measure of academic resilience for preservice teachers, which consists of two stages: the validity and reliability of the instrument; and continued with differences in academic resilience for preservice teachers among the fields of social, science, and language. Measurement instruments were given to lectures (eight experts) and students (n=236) from various universities in Medan, Indonesia. The content validity used V-Aiken, and construct validity used confirmatory factor analysis; reliability using the interclass correlation coefficient and internal consistency reliability. The results show that the constructs of composure, commitment, control, coordination, empathy, perseverance, and adaptive have excellent and accurate validity and reliability to measure academic resilience. The findings are specific that there are significant differences in the academic resilience for preservice teachers among field of sciences. Researchers imply that they can use these instruments appropriate and responsive to academic resilience for preservice teachers highlighting among the sciences' domain so that future research can be carried out to explore these differences.